Optimal capacitor placement in a dominant induction motor loads power system - Ardiaty Arief; Muhammad Bachtiar Nappu; Syahrul Mustafa; Erwin; Sarma Thaha (Energy Reports, 2022)
The challenge of optimal capacitor allocation is one of the complex problems in power systems, especially in large industries since they have many big capacity induction motors. In the literature, many works have been delivered for optimal capacitor placement, however, these works were simulated in a distribution network, not in an industry network with many large capacity induction motors. Therefore, this work proposes the optimal allocation of capacitors in a large industry with a significant amount of induction motor loads to minimize network losses. To determine the optimal capacitor location, this research uses the genetic algorithm (GA) method. This algorithm is interesting because of its simplicity and ability to discover optimal solutions comprehensively.